Pengaruh Self-Efficacy, Tekanan Ketaatan, Kompleksitas Tugas dan Pengalaman Auditor Terhadap Audit Judgment pada BPK RI Perwakilan Provinsi Jawa Timur - Nafila Maradipta; Oryza Tannar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The research aims to know the impact of self-efficacy, obedience pressure, task complexity and auditor’s experience to audit judgment and was conducted at the BPK Representative of east java. using a quantitative approach and involved a sample of 62 auditors selected through basic purposive sampling and Slovin formula. Data analysis relied on Partial Least Square (PLS) software. The result of this research reveal that self-efficacy and auditor’s experience is have a positive effect to audit judgment. This is because an auditor who has a good level of self-confidence and experience will find it easier to face existing challenges. Meanwhile obedience pressure and task complecity has no effect to audit judgment. This is because an auditor, when feeling under pressure or facing a variety of tasks, always maintains his independence. Because in the State Financial Audit Standards relating to audit work, they must be free in attitude, mentality and appearance from personal and organizational interference that can affect their independence.